Prenatal Diagnosis of Sandhoff Disease by Enzyme Analysis of Chorionic Villus Sample - Özkara, Asuman; Dikensoy, Ebru; Özlü, Tülay; Topçu, Meral; Çakar, Nur; Beksaç, Mehmet Sinan (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE AND STUDY DESIGN: The prenatal diagnosis of Sandhoff disease (SD) was performed in 14 fetuses of families by the analysis of chorionic villus sample obtained at 11-14 weeks of gestation. The diagnosis was based on the absence or near-absence of total hexosaminidase activity using fluorogenic synthetic substrate 4-methylumbelliferyl beta-D-glucosaminide. RESULTS: 7 fetuses were found to be affected and the pregnancies were terminated. The remaining seven fetuses were found to be normal. The diagnosis were confirmed after delivery by enzyme analysis of leucocytes isolated from peripheric blood. CONCLUSION: Chorionic villus sampling (CVS) is a safe and accurate method for the first trimester prenatal diagnosis of various genetical disorders if the amount of the chorionic villi taken is sufficient for enzyme analysis and if it is well separated from maternal blood or decidua. Hexosaminidase (Hex) assay using fluorogenic substrate is useful for specific prenatal diagnosis of SD.